Transcatheter tricuspid valve replacement: will it prevail? - Zhang, Xiling; Pommert, Nina Sophie; Meier, David; Sellers, Stephanie L.; Seoudy, Hatim; Müller, Oliver J.; Frank, Derk; Attmann, Tim; Berndt, Rouven; Warnecke, Gregor; Puehler, Thomas; Lutter, Georg (Frontiers in Cardiovascular Medicine, 2025)
Severe tricuspid regurgitation (TR) is a prevalent and challenging condition associated with poor survival outcomes and significant morbidity. Medical therapy alone often fails to provide adequate symptom relief, and stand-alone surgical intervention is linked to high mortality rates, making it a less favorable option unless combined with left-sided valve surgery. The advent of transcatheter tricuspid interventions has provided new therapeutic possibilities, particularly for high-risk patients who are ineligible for conventional surgery. However, many patients are still unsuited for transcatheter tricuspid repair or have only limited benefits from such procedures. In this context, Transcatheter tricuspid valve replacement (TTVR) has rapidly emerged as a promising alternative, offering the potential for more effective treatment outcomes. This review explores the latest advancements in TTVR devices, highlights key clinical findings, and discusses the challenges and limitations of this evolving strategy. Additionally, we address patient selection criteria, procedural outcomes, and future directions in the field, emphasizing the potential of TTVR to transform the management of severe TR.